EDUCATION, EMPLOYMENT AND AGE WITH MOTHER'S KNOWLEDGE OF STUNTING - sharah nursa'iidah (Fakultas Ilmu kesehatan UPN Veteran Jakarta, 2022)
Stunting is a condition of failed to grow caused by malnutrition in a long time so that toddlers become short of their height standard. The prevalence of stunting in Indonesia increases in 2018 to 30,8%. Mother's knowledge can be influenced by various factors including education, employment and age. The purpose of this research is to know the correlation of education, employment and age with the toddler mother's knowledge about stunting. This study uses an observational analytic method with a cross sectional design with a population of mothers with toddlers aged 0-5 years at Posyandu BMI 3. Samples were taken with a purposive sampling technique of 65 people. Bivariate analysis using chi square test with a significance level of 95%. The results showed there was a relationship between education and age with the knowledge of toddler mothers about stunting with p value of 0.003 < 0.05 and p value of 0.043 < 0.05. there was no relationship of work with the knowledge of toddler mothers about stunting with p value 0.191 > 0.05. The researcher recommends the next researcher to analyze other factors that can influence the mother's knowledge and conduct health interventions so that the mother's knowledge increases.